SARS-CoV-2 AMONG FRONT LINE HEALTH CARE WORKERS - Syed Waqar Abbas (Army Medical College Rawalpindi, 2020)
Objective: To determine clinical presentations and source among severe acute respiratory syndrome corona virus 2 positive health care workers of tertiary care hospital.